Child trafficking in China: a human rights-based perspective - Han, Ling (Springer, 2024)
This book provides a comprehensive view to those who are interested in human trafficking, child trafficking, and child protection in China. Based on over 2000 case laws from 1990 to 2020, this book provides an in-depth analysis of the causes, criminal patterns, and consequences of child trafficking happened in 30 provinces in China. It reveals a phenomenon that has not attracted much attention at the international level -- the trafficking of children, intranational and transnational, for resale and illegal adoption